2011
DOI: 10.1111/j.1582-4934.2010.01156.x
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide-rich diet improves physical endurance by up-regulating SUR2A in the heart

Abstract: SUR2A is an ATP-binding protein that serves as a regulatory subunit of cardioprotective ATP-sensitive K+ (KATP) channels. Based on signalling pathway regulating SUR2A expression and SUR2A role in regulating numbers of fully assembled KATP channels, we have suggested that nicotinamide-rich diet could improve physical endurance by stimulating SUR2A expression. We have found that mice on nicotinamide-rich diet significantly improved physical endurance, which was associated with significant increase in expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 33 publications
2
47
0
2
Order By: Relevance
“…* P \ 0.05 when compared to the wild type. WT wild type expression alone increase the number of K ATP channels (Du et al 2006(Du et al , 2010, increases heart resistance to b-adrenergic stress (Sukhodub et al 2010a) and hypoxia (Sukhodub et al 2010b). In turn, increased heart resistance to metabolic stress leads to improved physical endurance (Sukhodub et al 2010a).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…* P \ 0.05 when compared to the wild type. WT wild type expression alone increase the number of K ATP channels (Du et al 2006(Du et al , 2010, increases heart resistance to b-adrenergic stress (Sukhodub et al 2010a) and hypoxia (Sukhodub et al 2010b). In turn, increased heart resistance to metabolic stress leads to improved physical endurance (Sukhodub et al 2010a).…”
Section: Discussionmentioning
confidence: 98%
“…The treadmill endurance test consisted of a step-wise increase in velocity over time at constant incline (as described in Zingman et al 2002;Sukhodub et al 2010a). Inability to continue with physical activity was determined by the animal being unable to continue test irrespective of encouragement by electric shock.…”
Section: Treadmill Testmentioning
confidence: 99%
See 2 more Smart Citations
“…31 Researchers have found that the sole overexpression of the sulfonylurea receptor 2A protein generates a cardiac phenotype with more sarcolemmal K ATP channels, which is essential for preconditioning-induced cardioprotection, thus, increasing resistance to hypoxia and ischemia. [32][33][34][35][36] Therefore, it is possible that the sulfonylurea receptor 2A-mediated pathway that is regulated by Nampt acts assists in SIRT1-related cardioprotection.…”
Section: Upstream Mediators Nicotinamide Phosphoribosyltransferasementioning
confidence: 99%